Attachment theory in adult mental health : a guide to clinical practice - Danquah, Adam N.; Berry, Katherine (Abingdon, Oxon : Routledge, 2013)
"In the fifty years since its inception, John Bowlby's attachment theory has been powerfully influential on developmental psychology and, more recently, mental health. Bringing together the experience of a diverse range of mental health practitioners and researchers who routinely use attachment theory in their own work, Attachment Theory in Adult Mental Health provides a guide to using attachment theory in everyday practice. Adam N. Danquah and Katherine Berry present a wide-ranging and practical approach to the topic which includes studies on clinical practice, the provision of mental health services and accommodating intercultural perspectives. Section One covers the basics of attachment theory and practice. Section Two presents clinical problems and presentations including, among others, the treatment of depression, anxiety disorders, psychosis, personality disorder and eating disorders. Section Three addresses the needs of specific populations, discussing the influence of sociocultural factors like gender, ethnicity and age. Finally, Section Four examines the organisation and the practitioner, including using the theory to organise services and how individual therapists can integrate their own attachment histories into their approach. Including the most up-to-date theories and practice in the field, Attachment Theory in Adult Mental Health is ideal for psychologists and psychological therapists, counsellors, psychiatrists, occupational therapists, social workers and mental health service managers and commissioners"--Provided by publisher.
Attachment theory in therapeutic practice / Jeremy Holmes -- Attachment theory and compassion focused therapy for depression / Paul Gilbert -- Responding to threat : using attachment-related interventions in cognitive behavioural therapy of anxiety disorders / Gail Myhr -- Attachment theory and psychosis / Matthias Schwannauer and Andrew Gumley -- Understanding attachment, trauma, and dissociation in complex developmental trauma disorders / Kathy Steele and Onno van der Hart -- Attachment theory and personality disorders / Kenneth N. Levy, Kevin B. Meehan, and Christina M. Temes -- Disorganized attachment in the pathogenesis and the psychotherapy of borderline personality disorder / Giovanni Liotti -- Starving for affection : attachment narrative therapy with eating disorders / Rudi Dallos -- An attachment perspective on understanding and managing medically unexplained symptoms / Robert G. Maunder and Jonathan J. Hunter -- Bringing a gendered perspective to attachment theory in therapy / Susie Orbach -- Attachment in African Caribbean families / Lennox K. Thomas -- Meeting the mental health needs of older adults using the attachment perspective / Cecilia Poon -- Four pillars of security : attachment theory and practice in forensic mental health care / Gwen Adshead and Anne Aiyegbusi -- Using attachment theory to inform psychologically-minded care services, systems, and environments / Martin Seager -- Working from the inside out : the therapist's attachment history as a source of impasse, inspiration, and change / David Wallin.
Includes bibliographical references.
Keywords: Object Attachment; Adult; Mental Disorders -- therapy; Psychotherapy -- methods; mielenterveys; kiintymyssuhdeteoria; psykoterapia; mielenterveyshäiriöt; aikuiset